2022
DOI: 10.3390/biomedicines10010171
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response in IBD Patients Three and Six Months after Vaccination with the SARS-CoV-2 mRNA Vaccines mRNA-1273 and BNT162b2

Abstract: Severe acute respiratory syndrome coronovirus-2 (SARS-CoV-2) is the cause of the coronavirus disease 2019 (COVID-19) pandemic. Vaccination is considered the core approach to containing the pandemic. There is currently insufficient evidence on the efficacy of these vaccines in immunosuppressed inflammatory bowel disease (IBD) patients. The aim of this study was to investigate the humoral response in immunosuppressed IBD patients after COVID-19 mRNA vaccination. In this prospective study, IgG antibody levels (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
5
21
1
Order By: Relevance
“…Within-individual analyses also indicated that antibody levels decayed at an approximate rate of 400 AU/mL per week after 2 nd dose and 500 AU/mL per week after 3 rd dose. Decay of antibody titres following vaccine doses has been previously reported; 7,24 however, 3 rd dose antibody titres diminish from a considerably higher baseline as compared to the 2 nd dose vaccine. The threshold level for antibody titres to offer protection from an infection to SARS-CoV-2 is not known.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Within-individual analyses also indicated that antibody levels decayed at an approximate rate of 400 AU/mL per week after 2 nd dose and 500 AU/mL per week after 3 rd dose. Decay of antibody titres following vaccine doses has been previously reported; 7,24 however, 3 rd dose antibody titres diminish from a considerably higher baseline as compared to the 2 nd dose vaccine. The threshold level for antibody titres to offer protection from an infection to SARS-CoV-2 is not known.…”
Section: Discussionmentioning
confidence: 70%
“…26 Our data are consistent with previous studies in demonstrating diminished antibody responses following two doses of a SARS-CoV-2 vaccine for patients on anti-TNF therapy, combination immunosuppressive therapies, and corticosteroids. [6][7][8][9][10][11]24,27,28 In contrast, our study showed that the 3 rd dose of the vaccine yielded high antibody titres across all classes of medications used for maintenance of remission in IBD. However, administration of vaccine while concurrently taking prednisone yielded lower antibody response following 1 st , 2 nd , and 3 rd dose of the vaccine.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We therefore conclude that it is still unclear as to what extent long-term humoral response after SARS-CoV-2 vaccination is impacted by immunosuppressive therapies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 95%
“…In a previous study, we found an impaired humoral immune response 3 months after second vaccination with an mRNA vaccine, particularly in patients on anti-TNF therapy, compared with healthy control subjects. Six months after the second vaccination, we found, in a cohort of only 4 IBD patients and 7 healthy controls, the first indications of a significantly more divergent humoral immune response in IBD patients compared to healthy controls [ 19 ].…”
Section: Introductionmentioning
confidence: 99%